Transversalidade no Ensino Fundamental de Língua Portuguesa: representações da mulher trabalhadora em canções brasileiras - Fabiana Candida Borges (2019)
Based on the fact that many students have difficulties to understand what they read and also based on the fact that they need classes that are close to their reality, this research intends to develop strategies that lead them to broaden their reading skills. The work was based on Brazilian songs that approach the transversal themes Work and Cultural Plurality, of the National Curricular Parameters. For that, were analyzed Brazilian songs in which working women were protagonists characters. To carry out this work, the corpus was composed of initial questionnaire, field diary notes, set of reading activities, final questionnaire and evaluation questionnaire of the applied teaching plan. Based in the theoretical foundations of authors like Soares (2004), Red (2004), Kleiman (2007), Antunes (2010), Faria (2016), Fiorin (2005), Marcuschi (2002), Costa (2003), Camargos ), Coscarelli (2012), Dell'Isola (2013), Solé (1998) and NCP (BRAZIL, 1998), this research was carried out in two classes of 9th grade of the Escola Estadual Francisco Firmo de Matos, located in the city of Contagem. The results of this research point to the importance of addressing topics of social relevance in Portuguese language teaching. With the theme under study, "Work and Consumption" and "Cultural plurality" - proposed by the NCP - the students, in the midst of the discussions, were able to participate actively in the society in which they are inserted, they were able to modify their reality - a fact not previously observed. In addition, the applied teaching plan, besides raising the interest of the students, contributed in a significant way to the linguistic improvement of them. With each proposed activity, it was possible to observe the gradual evolution of the students. Although they did not reach 100%, they achieved results never before achieved. Thus, it is necessary to say that the development of reading skills, from Brazilian songs, contributes to the formation of active, thoughtful and reflective readers.